The convergence of transatlantic sanction policy against Iran. Issue 3 (2nd July 2016) - Lohmann, Sascha
Abstract: Between 1996 and 2012, cooperation between the United States (US) and the European Union (EU) on Iran sanctions underwent a dramatic shift from open disagreement to almost unanimous consensus. Whereas the US preferred negative sanctions throughout this period, the EU opted at first for using economic incentives and dialogue. The EU's diverging approach exemplified the overall preference for multilateralism and engagement strategies over unilateral coercive measures. Beginning in 2005, however, European sanction policy towards Iran converged with that of the US. In this article, I argue that the convergence of transatlantic sanction policy against Iran cannot be understood without the pressure employed by Washington. The US pressure campaign consisted of secondary sanctions against European companies. As necessary condition, US pressure has been a key external factor that complemented the EU's internal developments fostering a more coercive approach towards Tehran after the revelation of the Iranian nuclear programme in 2002 and the breakdown of the E3 (Great Britain, France and Germany) negotiations in 2005.